2021
DOI: 10.1108/gm-04-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

Independent board, gender diversity and bank performance in Nigeria: a system-GMM approach

Abstract: Purpose This study aims to examine the effects of board independence and gender diversity on bank performance in Nigeria. Design/methodology/approach The two-step system-generalized method moment was used to estimate the effect of board independence and gender diversity on bank performance in Nigeria using annual data of 15 deposit money banks from 2006 to 2018. Findings The results revealed that gender diversity is a significant positive predictor of bank performance, whereas board independence is a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…This is a method that has been very well received in the scientific community. Its main advantage lies in the fact that it relaxes the requirement for the “strict” exogeneity of inputs; they only have to be predetermined variables (Okoyeuzu et al 2021 ; Yao et al 2022 ). Thus, four models have been built with the following specifications: …”
Section: Methodsmentioning
confidence: 99%
“…This is a method that has been very well received in the scientific community. Its main advantage lies in the fact that it relaxes the requirement for the “strict” exogeneity of inputs; they only have to be predetermined variables (Okoyeuzu et al 2021 ; Yao et al 2022 ). Thus, four models have been built with the following specifications: …”
Section: Methodsmentioning
confidence: 99%
“…Other methodologies, like two-or three-stage least squares analysis (2SLS or 3SLS) for running simultaneous equations, produce inconsistent parameter estimates for dynamic models (García-Meca et al, 2015). Moreover, we solved two fundamental problems using the GMM system method -endogeneity and unobserved heterogeneity (Djalilov and Piesse, 2016;Okoyeuzu et al, 2021;Proença et al, 2020;Vieira et al, 2019). This methodology combines an equation in levels, where explanatory variables in first differences are used as instruments and an equation in first differences where level explanatory variables are used as instruments (Farag and Mallin, 2018) nonsignificant parameters jointly) (Munjal et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…When researching the characteristics of the CEO affecting bank performance in Indonesia and India, Endraswati (2018) and Handa (2019) suggested that commercial banks under female CEOs have lower business performance than commercial banks run by male CEO. According to Lafuente and Vaillant (2019) and Okoyeuzu et al (2021), gender diversity is essential in improving a commercial bank's business performance. However, this result is only meaningful when there is no participation of women in senior executive positions such as Chairman of the Board of Directors or Chief Executive Officer.…”
Section: Literature Reviewmentioning
confidence: 99%